1998
DOI: 10.1097/00005537-199812000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Noise‐induced hearing loss in young adults: The role of personal listening devices and other sources of leisure noise

Abstract: The majority of young users of personal listening devices are at low risk for substantive NIHL. Interpretation of the significance of these findings in relation to noise exposure must be made with caution. NIHL is an additive process and even subtle deficits may contribute to unequivocal hearing loss with continued exposure. The low prevalence of measurable deficits in this study group may not exclude more substantive deficits in other populations with greater exposures. Continued education of young people abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 17 publications
(30 reference statements)
6
55
1
2
Order By: Relevance
“…Studies have reported that PLD users have poorer hearing thresholds at high frequencies than non-users [8][9][10][11] . Other studies, however, did not find any evidence of NIHL among PLD users, [12][13][14][15][16] and audiogram thresholds of PLD users were comparable with those of non-users [13,16] .…”
Section: Introductionmentioning
confidence: 78%
“…Studies have reported that PLD users have poorer hearing thresholds at high frequencies than non-users [8][9][10][11] . Other studies, however, did not find any evidence of NIHL among PLD users, [12][13][14][15][16] and audiogram thresholds of PLD users were comparable with those of non-users [13,16] .…”
Section: Introductionmentioning
confidence: 78%
“…Various studies have shown that exposure to loud recreational music over prolonged periods of time leads to various effects on hearing and health [14][15][16][17][18][19]. These studies bought out recommendations for young people, who are perhaps not aware of the importance of good hearing to their future productivity and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] To date, evidence supporting the relationship between PMP use and hearing damage is mixed. 8,9 However, it is well documented that damage to the auditory system is a cumulative process and that once injury from loud noise is sufficiently severe enough to be measured, the loss is substantial and irreversible. 10,11 There have been several recent surveys regarding the self-reported use of earphones and portable entertainment devices and concerns about use.…”
mentioning
confidence: 99%